Exploration of gum ghatti-modified porous scaffolds for bone tissue engineering applications. (24th January 2020) - Lett, J. Anita; Sagadevan, Suresh; Shahnavaz, Zohreh; Latha, Muthiah Bavani; Alagarswamy, Karthick; Hossain, M. A. Motalib; Mohammad, Faruq; Johan, Mohd Rafie
Abstract : Taking advantage of the tissue engineering principles, the formed hydroxyl apatite-modified gum ghatti biomaterial with its porous nature, biocompatibility, and efficient mechanical properties can be potential for the bone repair and regeneration. Abstract : The tissue engineering (TE) field is an integrated discipline that makes use of principles from both engineering and natural sciences so as to achieve the replacement, repair, and improve the functions of diseased cells and the associated malfunctioning of tissues through the involvement of biological materials. In this context, the present study deals with the efficacy of biomaterial scaffold modified with a plant extract towards the regeneration of bone tissue. To that aim, we fabricated porous hydroxyapatite (HAP) scaffolds via a template-assisted polymer sponge replication technique using gum ghatti (GG) as a natural binding agent. With the use of a polymer replication method for the formation of porous HAP scaffolds, the unique formulation of water and GG plant extract as a solvent were examined. Thus, the formed scaffolds were thoroughly characterized to determine their structural, functional, and morphological, as well as mechanical properties by making use of many instrumental techniques. Following the physical characterization, the degradation stability and bioactivity of the scaffolds were assessed using simulated body fluid (SBF). Furthermore, some preliminary investigations such as cytotoxicity, biocompatibility, and cell proliferation tests were performed by seeding MDCK cell lines. From the analysis of the results, we indicate that the prepared HAP scaffold is a suitable material due to its ability to form a spongy bone architecture that is mechanically stable and has a highly interconnected micro and macroporous nature with a pore size of ∼200–500 μm. In addition, from the results of bioactivity and biocompatibility studies, therefore, we propose that the prepared unique formulations might be developed as suitable porous scaffold materials for bone tissue engineering applications.